Impact of selected determinants on the financial structure of the mining companies in the selected countries - Nicole Škuláňová (Review of Economic Perspectives, 2020)
Investigating the effects on the capital structure has been a widely debated topic for over a century. There are countless studies on this subject today. However, there is still a need to test more samples of companies, as the confirmation or rebuttal of assumptions depends on the industry, country, and size of the selected company. This research deals with the impact of five selected determinants - profitability, asset structure, non-debt tax shield, GDP growth rate, inflation, on the total, long-term and short-term debt of mining companies from eleven selected economies - eight countries from Central and Eastern Europe and three industry leaders from non-European countries. The analysis of data obtained from Orbis and the World Bank database covers the period 2009-2017. Correlation analysis and GMM methods are used to detect the dependencies of variables. Many countries show some links to selected types of debt. Some of these links are in line with the input assumptions, some unfortunately not.
Keywords: G32; 330; asset structure; depreciation; financial structure; GDP; inflation; profitability